MANFAAT EMOSI POSITIF BAGI GURU BIMBINGAN DAN KONSELING - Laurentius Purbo Christianto (Program Studi Bimbingan dan Konseling, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2018)
Guidance and counseling teachers are figures in schools that have an important role to teach positive emotion to student. In order to support that matter guidance and counseling teachers must have positive emotion. Guidance and counseling teachers that are vulnerable to negative emotion of student, become a challenge for guidance and counseling teachers to gain positive emotions. Guidance and counseling teachers should have positive emotions because positive emotions are beneficial to them, especially in cognitive, behavioral, adaptation, and health aspects. Guidance and counseling teachers who have positive emotions will also benefit to the student, especially on student academic achivement, teacher-student attachment, and solving student problem. Guidance and counseling teachers should have a positive purpose and expectation when performing their functions to gain positive emotions. Keywords : guidance and counseling teachers, positive emotion